Longitudinal association of dietary acid load with kidney function decline in an older adult population with metabolic syndrome - Valle-Hita, Cristina; Becerra-Tomás, Nerea; Díaz-López, Andrés; Vázquez-Ruiz, Zenaida; Megías, Isabel; Corella, Dolores; Goday, Albert; Martínez, J. Alfredo; Alonso-Gómez, Ángel M.; Wärnberg, Julia; Vioque, Jesús; Romaguera, Dora; et al. (Frontiers in Nutrition, 2022)
Background: Diets high in acid load may contribute to kidney function impairment. This study aimed to investigate the association between dietary acid load and one-year changes in glomerular filtration rate (eGFR) and urine albumin/creatinine ratio (UACR). Methods: Older adults with overweight/obesity and metabolic syndrome (mean age 65±5 years, 48% women) from the PREDIMED-Plus study who had available data on eGFR (n=5874) or UACR (n=3639) at baseline and after one year of follow-up were included in this prospective analysis. Dietary acid load was estimated as potential renal acid load (PRAL) and net endogenous acid production (NEAP) at baseline from a food frequency questionnaire. Linear and logistic regression models were fitted to evaluate the associations between baseline tertiles of dietary acid load and kidney function outcomes. One year-changes in eGFR and UACR were set as the primary outcomes. We secondarily assessed ≥10% eGFR decline or ≥10% UACR increase. Results: After multiple adjustments, individuals in the highest tertile of PRAL or NEAP showed higher one-year changes in eGFR (PRAL, β: -0.64 ml/min/1.73m2; 95% CI: -1.21 to -0.08 and NEAP, β: -0.56 ml/min/1.73m2; 95% CI: -1.13 to 0.01) compared to those in the lowest category. No associations with changes in UACR were found. Participants with higher levels of PRAL and NEAP had significantly higher odds of developing ≥10% eGFR decline (PRAL, OR: 1.28; 95% CI: 1.07 to 1.54 and NEAP, OR: 1.24; 95% CI: 1.03 to 1.50) and ≥10 % UACR increase (PRAL, OR: 1.23; 95% CI: 1.04 to 1.46) compared to individuals with lower dietary acid load. Conclusions: Higher PRAL and NEAP were associated with worse kidney function after one year of follow-up as measured by eGFR and UACR markers in an older Spanish population with overweight/obesity and metabolic syndrome.